Social evolution and sex allocation theory - Alpedrinha, J (2012)
The study of sex allocation is one of the most successful areas in evolutionary biology: its theoretical predictions have been supported by experimental, observational and comparative approaches. Here, I develop sex allocation theory as follows: (1) I use fertility insurance theory to predict the sex ratio strategy of the malaria parasite, in response to human medical interventions that increase mortality and decrease fertility of the parasite’s various sexual stages; (2) Haplodiploidy has been suggested as a driver of the evolution of eusociality, as under this genetic system a female may be more related to her sister than to her own offspring. I examine a model considering queen versus worker control over the sex ratio of the colony and show that haplodiploidy alone does not explain the evolution of helping; (3) I follow up this study of the haplodiploidy hypothesis by examining the idea that split-sex ratios may favour the evolution of eusociality in haplodiploid species. I study the two mechanisms of split sex ratios, that are found in natural populations and may have been important in the transition to eusociality: queen virginity and queen replacement. I focus on the impact of worker reproduction by considering the effect of woker producing a fraction of the colony offspring and by considering variation in the workers’ offspring sex ratio. My analysis shows that worker reproduction does not promote the evolution of helping in haplodiploid species; (4) I examine the evolution and function of a sterile soldier caste in parasitoid wasps from the genus Encyrtidae. Two main functions have been hypothesized for the emergence of soldiers: spiteful mediation of a sex ratio conflict in mixed-sex broods, and altruistic protection and 7 facilitation of the development of relatives. I develop a model considering variation in the oviposition behaviour of females, that may produce single-sex or mixed-sex broods. I show that, in accordance with previous theory, females are expected to produce more soldiers than males, under the sex ratio conflict hypothesis. I also show that one of the consequences of this costly conflict is that females are favoured to produce single-sex broods over mixed-sex broods.